Juridical Analysis Of The Crime Of Forging A Package C Diploma And Certificate Of The Results Of The Equality Education Exam In The Election Of Keuchik Gampong Alue Ie Mirah Pante Bidari District East Aceh Regency - Munawir; Yasmirah Mandasari Saragih (International Journal of Society and Law, 2024)
A diploma certifies that an individual has completed a level of education, serving as a key indicator of their qualifications. However, the modern era has seen a rise in diploma forgery, facilitated by technological advancements. This crime is a subset of letter forgery and is explicitly addressed in Indonesian law, including the Criminal Code (KUHP) and Law Number 20 of 2003 on the National Education System. Diploma forgery not only undermines legal norms but also violates academic ethics and the integrity of educational institutions. A notable case is Saifuddin Razali's use of a forged Package C diploma during the 2018 election for Keuchik Gampong Alue Ie Mirah, resulting in a four-month prison sentence. This study, titled "Juridical Analysis of the Crime of Counterfeiting Package C Diplomas and Certificates of Equivalency Education Exam Results in the Election of Keuchik Gampong Alue Ie Mirah, Pante Bidari District, East Aceh Regency," examines the legal implications and the broader impact of diploma forgery on society and education. The research highlights the importance of stringent legal measures to curb this malpractice and protect the integrity of academic credentials.